ATO-TiO2 coated glass bead, preparation method and application of ATO-TiO2 coated glass bead in preparation of conductive coating

By covering the ATO-TiO2 composite layer on the surface of the glass beads, forming the ATO-TiO2-covered glass beads, the problems of high cost and poor stability of conductive fillers in existing conductive coatings are solved, and the performance and production cost are achieved Low effect.

CN119430662AInactive Publication Date: 2025-02-14HUBEI YAXING ELECTRONIC MATERIALS CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411680229.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Among existing conductive coatings, metal-based conductive fillers such as silver powder and copper powder have high cost and poor stability, while carbon-based conductive fillers such as carbon black are prone to flocculation and dispersion in the coating, affecting uniformity and conductive properties.

Method used

By covering the ATO-TiO2 composite layer on the surface of the glass beads, ATO-TiO2-coated glass beads are formed, and used as a new conductive filler for the preparation of conductive coatings.

Benefits of technology

The conductive filler has excellent conductivity and resistance, can metallize the surface of polymer materials, and has conductive properties, and at the same time eliminates static charges. It is simple to operate, easy to obtain raw materials, and low production cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005148137270000081
    Figure BDA0005148137270000081
Patent Text Reader

Abstract

The invention discloses ATO-TiO2 coated glass beads, a preparation method and application of the ATO-TiO2 coated glass beads in preparation of conductive coatings, and belongs to the technical field of conductive coatings. According to the preparation method, titanium dioxide and doped tin oxide are respectively used for coating glass beads, so that ATO-TiO2 coated glass beads are formed. According to the preparation method of the ATO-TiO2 coated glass beads disclosed by the invention, when the mass ratio of SnCl4. 5H2O to SbCl3 is 100: 10, the reaction pH value is 2, the reaction temperature is 70 DEG C, and the calcination temperature is 600 DEG C, the prepared ATO-TiO2 coated glass beads have the best conductivity. The ATO-TiO2 coated glass beads prepared by the preparation method can be used as a conductive filler for preparing a conductive coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of conductive coatings, and in particular to an ATO-TiO2 coated glass microsphere, a preparation method and an application thereof in the preparation of conductive coatings. Background Art

[0002] Conductive coating is a new type of coating produced in the late 1960s. It is composed of base material, filler, solvent and additive, and at least one of the components has the ability to conduct electricity. With the development of science and technology, the application field of conductive coating is becoming wider and wider. For example, conductive coating can be used for printed circuit boards, integrated circuit packaging, liquid crystal display, etc. to improve the conductivity and stability of products; in the field of aerospace, conductive coating can be used for surface coating of aircraft, satellites and other aircraft to play the role of electromagnetic shielding and antistatic to ensure flight safety.

[0003] Conductive fillers are key components that enable conductive coatings to have both conductive properties and electromagnetic shielding properties. Currently, the most commonly used conductive fillers in the market are metal-based conductive fillers and carbon-based conductive fillers. Among metal-based conductive fillers, silver powder is often used as a filler for conductive coatings due to its excellent conductive properties, but it is expensive and has high production costs, making it unsuitable for large-scale applications. Although copper powder is cheaper than silver powder as a conductive filler, it has poor stability and is easily oxidized during production and processing, so its application prospects are not optimistic. Among carbon-based conductive fillers, carbon black has certain conductivity, but it is easy to flocculate and difficult to disperse in the coating, thus affecting the uniformity of the coating and the final conductive properties. Other carbon-based conductive fillers also have the characteristics of insolubility and difficulty in processing, which limits their application in conductive coatings.

[0004] Therefore, it is necessary to develop new conductive fillers with excellent conductive properties and low production costs to meet market needs. Summary of the invention

[0005] In view of this, the purpose of the present application is to provide an ATO-TiO2 coated glass microsphere, a preparation method and its application in the preparation of conductive coatings. The preparation method of the ATO-TiO2 coated glass microspheres is to coat the glass microspheres with titanium dioxide (TiO2) and doped tin oxide (ATO) respectively to form a new type of conductive filler, which has strong tolerance and conductivity and can be used in the preparation of conductive coatings.

[0006] In order to achieve or at least partially achieve the above objectives, the present application provides the following technical solutions:

[0007] In a first aspect, the present application provides a method for preparing ATO-TiO2 coated glass microspheres, comprising the following steps:

[0008] Preparation of TiO2-coated glass microspheres;

[0009] Adding TiO2-coated glass microspheres into deionized water to form a first suspension;

[0010] Add tin salt and antimony salt to the first suspension, mix well, adjust the pH to 8-10, and let stand until the reaction is complete to obtain a second suspension;

[0011] The second suspension was filtered, and the obtained precipitate was washed with deionized water and then dried to obtain the precursor of ATO-TiO2 coated glass microspheres;

[0012] The precursor of the ATO-TiO2 coated glass microspheres is calcined to finally obtain the ATO-TiO2 coated glass microspheres.

[0013] In a second aspect, the present application provides an ATO-TiO2 coated glass microsphere, which is prepared by the above-mentioned preparation method.

[0014] In a third aspect, the present application provides the use of the above-mentioned ATO-TiO2 coated glass microspheres in the preparation of conductive coatings.

[0015] The ATO-TiO2 coated glass microspheres, preparation method and application thereof in preparing conductive coatings provided in the present application have at least the following beneficial effects compared with the prior art:

[0016] 1. The present application provides a method for preparing ATO-TiO2 coated glass microspheres, in which titanium dioxide (TiO2) and doped tin oxide (ATO) are coated on the surface of the glass microspheres to form a conductive filler with excellent conductive properties.

[0017] 2. The ATO-TiO2 coated glass microspheres provided in the present application can be used as conductive fillers in the preparation of conductive coatings, so as to metallize the surface of polymer materials that do not have conductive properties and make them conductive, while also being able to eliminate static charges and avoid harm.

[0018] 3. The preparation method of ATO-TiO2 coated glass microspheres provided in this application is simple to operate, the raw materials are readily available, and the production cost is low. DETAILED DESCRIPTION

[0019] In order to make the purpose, technical solution and advantages of the present application more clear, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described here are only used to explain the present application and are not used to limit the present application.

[0020] Those skilled in the art will appreciate that, unless otherwise stated, the words "said", "the", and "the aforementioned" used in the text of the present application may also include plural forms. It should be further understood that the wording "including" used in the specification of the present application means the presence of the features, steps, and operations, but does not exclude the presence or addition of one or more other features, integers, and steps.

[0021] In the text of this application, the terms "first", "second" and the like are used to distinguish between identical or similar items with substantially the same functions and effects. This is only for the purpose of clearly describing the technical solutions of the embodiments of this application, and shall not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features.

[0022] Those skilled in the art will appreciate that, for any specific experimental steps or conditions not specified in the examples, the experiments may be carried out according to the conventional experimental steps or conditions described in the literature in the art; any raw materials or instruments used without specifying the manufacturer are conventional products that can be purchased commercially.

[0023] Those skilled in the art will understand that, unless otherwise specified in the present application, when a numerical range is given in an embodiment, both endpoints of each numerical range and any value between the two endpoints may be selected. Unless otherwise defined, all technical and scientific terms used in this application are consistent with the prior art mastery of those skilled in the art and the records of this application, and any methods, equipment and materials of the prior art similar or equivalent to the methods, equipment and materials described in the embodiments of this application may also be used to implement this application.

[0024] The term "glass microspheres" refers to a new type of material with a wide range of uses and special properties. Its main component is borosilicate, with a particle size of 10 to 250 μm and a wall thickness of 1 to 2 μm. It has the advantages of light weight, low thermal conductivity, high strength, and good chemical stability. Its surface has been specially treated to have lipophilic and hydrophobic properties, and it is very easy to disperse in organic material systems.

[0025] Glass microspheres have excellent dispersibility in coatings. Based on this, the applicant has formed ATO-TiO2 coated glass microspheres by coating the surface of traditional glass microspheres with an ATO-TiO2 composite conductive layer. The glass microspheres have excellent conductive properties and can be used to make conductive fillers. The glass microspheres can be further dispersed in polymer-based coatings to give the coatings conductive properties, electromagnetic shielding, anti-static properties, and other functions, thereby forming conductive coatings.

[0026] Based on this, an embodiment of the present application provides a method for preparing ATO-TiO2 coated glass beads, comprising the following steps: (1) preparing TiO2 coated glass beads; (2) adding the TiO2 coated glass beads to deionized water to form a first suspension; (3) adding tin salt and antimony salt to the first suspension, mixing evenly, adjusting the pH, and standing for the reaction to be complete to obtain a second suspension; (4) filtering the second suspension, washing the obtained precipitate with deionized water, and then drying to obtain a precursor of the ATO-TiO2 coated glass beads; (5) calcining the precursor of the ATO-TiO2 coated glass beads to finally obtain the ATO-TiO2 coated glass beads.

[0027] In certain embodiments, the specific steps of step (1) preparing TiO2-coated glass microspheres are: mixing glass microspheres with deionized water to obtain a mixed solution; adding sodium dodecylbenzene sulfonate to the mixed solution and mixing evenly to obtain a suspension of glass microspheres; heating the suspension to 55-65°C, adding titanium sulfate (Ti(SO4)2) solution to the suspension, adjusting the pH to neutral, reacting for 6-8 hours, and filtering to obtain a precipitate; washing the precipitate with deionized water for 2-3 times, and drying at 100-120°C to obtain glass microsphere powder; calcining the glass microsphere powder at 600-800°C for 2-4 hours to finally obtain TiO2-coated glass microspheres.

[0028] In certain embodiments, the tin salt in step (3) is tin tetrachloride pentahydrate (SnCl4·5H2O), and the antimony salt is antimony trichloride (SbCl3).

[0029] In some embodiments, the mass ratio of SnCl4·5H2O to SbCl3 added in step (3) is 100:8-11.

[0030] In certain preferred embodiments, the mass ratio of SnCl4·5H2O to SbCl3 added in step (3) is 100:10.

[0031] In certain embodiments, the pH value adjusted in step (3) is 1-3.

[0032] In some preferred embodiments, the adjusted pH value is 1.5 to 2. When the pH value is 1.5 to 2, SnCl4 and SbCl3 in the solution react completely with water. 4+ and Sb 3+ The above ratio can be used for co-precipitation, which is conducive to the formation of doped tin oxide film and adsorption on the surface of TiO2, thereby forming stable ATO-TiO2 coated glass microspheres; if the pH of the solution system is too low and the acidity is too strong, SnCl4 cannot completely react with water, and Sn 4+ and Sb 3+It is impossible to precipitate together according to the ideal ratio, resulting in the inability to form stable ATO-TiO2 coated glass microspheres with good conductive properties; if the pH value is too high, the TiO2 coated glass microspheres are prone to flocculation and the dispersion will deteriorate, which will lead to Sn 4+ and Sb 3+ It is difficult to co-precipitate TiO2-coated glass microspheres to form stable ATO-TiO2-coated glass microspheres with good conductive properties.

[0033] In certain embodiments, the temperature during the reaction in step (3) is 60-80°C. If the reaction temperature is too high, the hydrolysis rate of SnCl4 will be accelerated. Due to the high reaction temperature, the kinetic energy of Sn / Sb hydrate particles when colliding increases, and it is easier to overcome the potential barrier between each other and aggregate, which is not conducive to coating on the surface of TiO2. When the reaction temperature is 60-80°C, the hydrolysis rate decreases appropriately, and the Sn / Sb hydrate particles produced by hydrolysis become finer, which is conducive to adsorption and coating on the TiO2 surface, thereby forming stable, ATO-TiO2 coated glass microspheres with good conductive properties. However, if the temperature drops to a lower level, the hydrolysis rate will be slower, and the smaller Sn / Sb hydrate particles will also lead to the aggregation of particles, the agglomeration phenomenon will be aggravated, and the surface adsorption of impurity ions will increase, which is not conducive to the cleaning of subsequent steps.

[0034] In certain embodiments, the calcination temperature in step (5) is 500-700°C.

[0035] In some preferred embodiments, the calcination temperature in step (5) is 600°C. The conductivity of the powder increases significantly with the increase of calcination temperature because the solid phase doping reaction efficiency increases with the increase of temperature, which is beneficial to the Sb in the SnO2 lattice coated on the TiO2 surface. 3+ Converted to Sb 5+ The increase in concentration increases the concentration of conductive carriers in the ATO-TiO2 coated glass microspheres; however, when the calcination temperature is too high (over 700°C), the expansion coefficients of SnO2 and TiO2 in the ATO-TiO2 coated glass microspheres are inconsistent, which will cause the two to separate, resulting in poor conductivity.

[0036] Based on this, the present application provides an ATO-TiO2 coated glass microsphere, which is prepared by the above-mentioned preparation method.

[0037] Based on this, the present application provides the use of the above-mentioned ATO-TiO2 coated glass microspheres in the preparation of conductive coatings.

[0038] In these applications, the ATO-TiO2 coated glass microspheres prepared in the embodiments of the present application are used as conductive filler components in conductive coatings, and different performance requirements are achieved by adjusting the mass ratio of the glass microspheres with other components (such as emulsifiers, preservatives, curing agents, antibacterial agents, thickeners, and one or more organic solvents).

[0039] The technical solution of the present application and the technical effects achieved are described in detail below through more specific embodiments.

[0040] Example 1

[0041] This embodiment provides a method for preparing ATO-TiO2 coated glass microspheres, and the specific steps are as follows:

[0042] (1) First, TiO2-coated glass microspheres were prepared by mixing 5 g of glass microspheres with 50 g of deionized water to obtain a mixed solution; 0.5 g of sodium dodecylbenzene sulfonate was added to the mixed solution and mixed evenly to obtain a suspension of glass microspheres; the suspension was heated to 60°C, 500 mL of 0.1 mol / L titanium sulfate solution was added to the suspension, the pH was adjusted to 7, the reaction was performed for 6 h, and a precipitate was obtained by filtering; the precipitate was washed with deionized water for 2 to 3 times, and then dried at 110°C to obtain glass microsphere powder; the glass microsphere powder was calcined at 600°C for 3 h to finally obtain TiO2-coated glass microspheres T1;

[0043] (2) adding the TiO2-coated glass microspheres T1 obtained in (1) to deionized water to form a first suspension;

[0044] (3) adding 10 g SnCl4·5H2O and 1 g SbCl3 to the first suspension, mixing well, adjusting the pH value to 2, and reacting at 70°C for 30 min to obtain a second suspension;

[0045] (4) Filter (3) to obtain a second suspension, and wash the obtained precipitate with deionized water several times until there is no Cl in the filtrate - , and then dried at 80°C to obtain the precursor of ATO-TiO2-coated glass microspheres;

[0046] (5) The precursor of the ATO-TiO2 coated glass microspheres obtained in (4) was calcined at a temperature of 600° C. for 3 h to finally obtain ATO-TiO2 coated glass microspheres A1.

[0047] Example 2

[0048] This embodiment provides a method for preparing ATO-TiO2 coated glass microspheres, and the specific steps are as follows:

[0049] (1) Prepare TiO2-coated glass microspheres T2 according to step (1) in Example 1;

[0050] (2) adding the TiO2-coated glass microspheres T2 obtained in (1) to deionized water to form a first suspension;

[0051] (3) adding 10 g SnCl4·5H2O and 0.8 g SbCl3 to the first suspension, mixing well, adjusting the pH value to 2, reacting at 70°C for 30 min, and obtaining a second suspension;

[0052] (4) Filter (3) to obtain a second suspension, and wash the obtained precipitate with deionized water several times until there is no Cl in the filtrate - , and then dried at 80°C to obtain the precursor of ATO-TiO2-coated glass microspheres;

[0053] (5) The precursor of the ATO-TiO2 coated glass microspheres obtained in (4) was calcined at a temperature of 600° C. for 3 h to finally obtain ATO-TiO2 coated glass microspheres A2.

[0054] Example 3

[0055] This embodiment provides a method for preparing ATO-TiO2 coated glass microspheres, and the specific steps are as follows:

[0056] (1) Prepare TiO2-coated glass microspheres T3 by referring to step (1) in Example 1;

[0057] (2) adding the TiO2-coated glass microspheres T3 obtained in (1) to deionized water to form a first suspension;

[0058] (3) adding 10 g SnCl4·5H2O and 1.1 g SbCl3 to the first suspension, mixing well, adjusting the pH value to 2, reacting at 70°C for 30 min, and obtaining a second suspension;

[0059] (4) Filter (3) to obtain a second suspension, and wash the obtained precipitate with deionized water several times until there is no Cl in the filtrate - , and then dried at 80°C to obtain the precursor of ATO-TiO2-coated glass microspheres;

[0060] (5) The precursor of the ATO-TiO2 coated glass microspheres obtained in (4) was calcined at a temperature of 600° C. for 3 h to finally obtain ATO-TiO2 coated glass microspheres A3.

[0061] Example 4.

[0062] This embodiment provides a method for preparing ATO-TiO2 coated glass microspheres, and the specific steps are as follows:

[0063] (1) Prepare TiO2-coated glass microspheres T4 by referring to step (1) in Example 1.

[0064] (2) adding the TiO2-coated glass microspheres T4 obtained in (1) to deionized water to form a first suspension;

[0065] (3) adding 10 g SnCl4·5H2O and 1 g SbCl3 to the first suspension, mixing well, adjusting the pH value to 1, and reacting at 70°C for 30 min to obtain a second suspension;

[0066] (4) Filter (3) to obtain a second suspension, and wash the obtained precipitate with deionized water several times until there is no Cl in the filtrate - , and then dried at 80°C to obtain the precursor of ATO-TiO2-coated glass microspheres;

[0067] (5) The precursor of the ATO-TiO2 coated glass microspheres obtained in (4) was calcined at a temperature of 600° C. for 3 h to finally obtain ATO-TiO2 coated glass microspheres A4.

[0068] Example 5.

[0069] This embodiment provides a method for preparing ATO-TiO2 coated glass microspheres, and the specific steps are as follows:

[0070] (1) Prepare TiO2-coated glass microspheres T5 by referring to step (1) in Example 1.

[0071] (2) adding the TiO2-coated glass microspheres T5 obtained in (1) to deionized water to form a first suspension;

[0072] (3) adding 10 g SnCl4·5H2O and 1 g SbCl3 to the first suspension, mixing well, adjusting the pH value to 3, and reacting at 70°C for 30 min to obtain a second suspension;

[0073] (4) Filter (3) to obtain a second suspension, and wash the obtained precipitate with deionized water several times until there is no Cl in the filtrate - , and then dried at 80°C to obtain the precursor of ATO-TiO2-coated glass microspheres;

[0074] (5) The precursor of the ATO-TiO2 coated glass microspheres obtained in (4) was calcined at a temperature of 600° C. for 3 h to finally obtain ATO-TiO2 coated glass microspheres A5.

[0075] Example 6

[0076] This embodiment provides a method for preparing ATO-TiO2 coated glass microspheres, and the specific steps are as follows:

[0077] (1) Prepare TiO2-coated glass microspheres T6 by referring to step (1) in Example 1.

[0078] (2) adding the TiO2-coated glass microspheres T6 obtained in (1) to deionized water to form a first suspension;

[0079] (3) adding 10 g SnCl4·5H2O and 1 g SbCl3 to the first suspension, mixing well, adjusting the pH value to 2, reacting at 60°C for 30 min, and obtaining a second suspension;

[0080] (4) Filter (3) to obtain a second suspension, and wash the obtained precipitate with deionized water several times until there is no Cl in the filtrate - , and then dried at 80°C to obtain the precursor of ATO-TiO2-coated glass microspheres;

[0081] (5) The precursor of the ATO-TiO2 coated glass microspheres obtained in (4) was calcined at a temperature of 600° C. for 3 h to finally obtain ATO-TiO2 coated glass microspheres A6.

[0082] Example 7

[0083] This embodiment provides a method for preparing ATO-TiO2 coated glass microspheres, and the specific steps are as follows:

[0084] (1) Prepare TiO2-coated glass microspheres T7 according to step (1) in Example 1.

[0085] (2) adding the TiO2-coated glass microspheres T7 obtained in (1) to deionized water to form a first suspension;

[0086] (3) adding 10 g SnCl4·5H2O and 1 g SbCl3 to the first suspension, mixing well, adjusting the pH value to 2, and reacting at 80°C for 30 min to obtain a second suspension;

[0087] (4) Filter (3) to obtain a second suspension, and wash the obtained precipitate with deionized water several times until there is no Cl in the filtrate - , and then dried at 80°C to obtain the precursor of ATO-TiO2-coated glass microspheres;

[0088] (5) The precursor of the ATO-TiO2 coated glass microspheres obtained in (4) was calcined at a temperature of 600° C. for 3 h to finally obtain ATO-TiO2 coated glass microspheres A7.

[0089] Example 8

[0090] This embodiment provides a method for preparing ATO-TiO2 coated glass microspheres, and the specific steps are as follows:

[0091] (1) Prepare TiO2-coated glass microspheres T8 according to step (1) in Example 1.

[0092] (2) adding the TiO2-coated glass microspheres T8 obtained in (1) to deionized water to form a first suspension;

[0093] (3) adding 10 g SnCl4·5H2O and 1 g SbCl3 to the first suspension, mixing well, adjusting the pH value to 2, and reacting at 70°C for 30 min to obtain a second suspension;

[0094] (4) Filter (3) to obtain a second suspension, and wash the obtained precipitate with deionized water several times until there is no Cl in the filtrate - , and then dried at 80°C to obtain the precursor of ATO-TiO2-coated glass microspheres;

[0095] (5) The precursor of the ATO-TiO2 coated glass microspheres obtained in (4) was calcined at a temperature of 700°C for 3 h to finally obtain ATO-TiO2 coated glass microspheres A8.

[0096] Example 9

[0097] This embodiment provides a method for preparing ATO-TiO2 coated glass microspheres, and the specific steps are as follows:

[0098] (1) Prepare TiO2-coated glass microspheres T9 according to step (1) in Example 1.

[0099] (2) adding the TiO2-coated glass microspheres T1 obtained in (1) to deionized water to form a first suspension;

[0100] (3) adding 10 g SnCl4·5H2O and 1 g SbCl3 to the first suspension, mixing well, adjusting the pH value to 2, and reacting at 70°C for 30 min to obtain a second suspension;

[0101] (4) Filter (3) to obtain a second suspension, and wash the obtained precipitate with deionized water several times until there is no Cl in the filtrate -, and then dried at 80°C to obtain the precursor of ATO-TiO2-coated glass microspheres;

[0102] (5) The precursor of the ATO-TiO2 coated glass microspheres obtained in (4) was calcined at a temperature of 500° C. for 3 h to finally obtain ATO-TiO2 coated glass microspheres A9.

[0103] The volume resistivity of the ATO-TiO2 coated glass beads A1 to A9 prepared in the above examples was measured respectively, and the test method was as follows:

[0104] Fill the conductive paint into a glass tube with an inner diameter of 5mm and a length of 50mm, connect the two ends with wires, remove the glass tube after curing, and measure the resistance R at both ends with a digital meter with an accuracy of 0.01Ω. v , calculate the volume resistivity, the calculation formula is as follows:

[0105] P v (Volume resistivity, unit: Ω·cm) = R v L / A, where R v is the volume resistance (unit: Ω), A is the cross-sectional area of ​​the glass tube (unit: cm 2 ), L is the length of the glass tube (unit: cm).

[0106] The volume resistivity results of the final test and the key parameters of each embodiment are shown in Table 1 below.

[0107] Table 1

[0108]

[0109] From the data in Table 1, it can be seen that the volume resistivity of the ATO-TiO2 coated glass microspheres prepared in Examples 1 to 9 is relatively low, all lower than 20Ω·cm, indicating that the ATO-TiO2 coated glass microspheres A1 to A9 have good conductivity and can be used as conductive fillers to make conductive coatings. Comparing the volume resistivity results of A1 to A3, it is found that when the mass ratio of SnCl4·5H2O to SbCl3 is 100:10 and other condition parameters are consistent, the volume resistivity is the lowest; comparing the volume resistivity results of A1, A4, and A5, it is found that when the reaction pH value is 2 and other condition parameters are consistent, the volume resistivity is the lowest; comparing the volume resistivity results of A1, A6, and A7, it is found that when the reaction temperature is 70°C and other condition parameters are consistent, the volume resistivity is the lowest; comparing the volume resistivity results of A1, A8, and A9, it is found that when the calcination temperature is 600°C and other condition parameters are consistent, the volume resistivity is the lowest. Therefore, when preparing ATO-TiO2 coated glass beads, when the mass ratio of SnCl4·5H2O to SbCl3 is 100:10, the reaction pH is 2, the reaction temperature is 70°C, and the calcination temperature is 600°C, the ATO-TiO2 coated glass beads produced by the preparation method provided in Example 1 have the best conductive properties.

[0110] In summary, the ATO-TiO2 coated glass microspheres provided in the embodiments of the present application have excellent conductive properties, can be used to make conductive fillers, and are further used in the preparation of conductive coatings.

[0111] The present application is described in detail above. Specific examples are used in this article to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the present application and its core ideas. It should be pointed out that for ordinary technicians in this technical field, without departing from the principles of the present application, several improvements and modifications can be made to the present application, and these improvements and modifications also fall within the scope of protection of the claims of the present application.

Claims

1. A method for preparing ATO-TiO2 coated glass microspheres, characterized in that: The following steps are involved: Preparation of TiO2-coated glass microspheres; Adding TiO2-coated glass microspheres into deionized water to form a first suspension; Add tin salt and antimony salt to the first suspension, mix well, adjust pH, and stand for complete reaction to obtain a second suspension; The second suspension was filtered, and the obtained precipitate was washed with deionized water and then dried to obtain the precursor of ATO-TiO2 coated glass microspheres; The precursor of the ATO-TiO2 coated glass microspheres is calcined to finally obtain the ATO-TiO2 coated glass microspheres.

2. The preparation method according to claim 1, characterized in that: The specific steps of preparing TiO2-coated glass microspheres are: mixing glass microbeads with deionized water to obtain a mixed solution; Adding sodium dodecylbenzene sulfonate to the mixed solution, mixing evenly, and obtaining a suspension of glass microbeads; The suspension is heated to 55-65° C., a titanium sulfate solution is added to the suspension, the pH is adjusted to neutral, the reaction is carried out for 6-8 hours, and a precipitate is obtained by filtering; the precipitate is washed with deionized water for 2-3 times, and then dried at 100-120° C. to obtain a glass microbead powder; The glass microsphere powder is calcined at 600-800° C. for 2-4 hours to finally obtain TiO2-coated glass microspheres.

3. The preparation method according to claim 1, characterized in that: The tin salt is SnCl4·5H2O, and the antimony salt is SbCl3.

4. The preparation method according to claim 3, characterized in that: The mass ratio of the added SnCl4·5H2O to SbCl3 is 100:8-11.

5. The preparation method according to claim 1, characterized in that The adjusted pH value is 1-3.

6. The preparation method according to claim 1, characterized in that: The temperature of the reaction of the tin salt and the antimony salt in the first suspension is 60-80°C.

7. The preparation method according to claim 1, characterized in that: The calcination temperature is 500-700°C.

8. The preparation method according to claim 1, characterized in that: The calcination temperature is 600°C.

9. A glass microsphere coated with ATO-TiO2, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the ATO-TiO2 coated glass microspheres according to claim 9 in the preparation of conductive coatings.

Citation Information

Cited By

  • Preparation method of high-performance modified barium titanate

    CN120794647A